STUDENTS’ PERCEPTIONS ON ENHANCING SPEAKING SKILLS VIA VIDEO RECORDING TASKS - Engelina Salainti; Nofry Frans; Vera Wahani (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Speaking skills are crucial in English language learning for several reasons. They play an important role in effective communication, self-development, and professional fluency. They are the basis of communication, enabling the students to express their thoughts, characters, and feelings effectively. Developing speaking skills strongly will build self-confidence and facilitate a better relationship. Effective communication helps to express ideas clearly and convincingly. However, to understand the students’ perceptions, challenges in speaking skills are other parts that need more research. This research aims to find out the students' perceptions on enhancing speaking skills via video recording tasks. This research applied a qualitative method. The data was collected through an interview. 10 students who participated in the interview.